(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
4-(4-(R-carboxymethyl)-1H-1,2,3-triazol-1-yl)benzoic acid, 4-(4-(hydroxymethyl)1H1,2,3-triazol-1-yl) Synthesis based on mutual 1,3-dipolar cycloaddition in the presence of copper (I) iodide as a catalyst in the synthesis of benzoic acid derivatives. Carrying out an etherification reaction with ethyl alcohol to the synthesized 1,2,3-triazole derivative. The structure of the obtained substances and the use of modern physical research methods